Brand and product integration in horizontal mergers and acquisitions. (28th January 2010) - Vu, Dung Anh; Shi, Yongjiang; Gregory, Mike
This paper aims to understand integration of brands and products after Mergers and Acquisitions (M&As). The paper identifies four different strategies for integrating brands and products: 'Choice', 'Growth Maximisation', 'Harmonisation' and 'Foundation'. These strategies act as strategic directions for firms to follow and to integrate brands and products in post-horizontal M&As in order to create and deliver value and competitiveness. Each main integration strategy contains a set of different sub-strategies (18 in total) which aim to achieve the same objective set by its umbrella integration strategy. The paper also builds the linkage between the integration sub-strategies and the two currently-in-use views – positioning and resource-based – from the strategic management perspective. Through in-depth case studies and analyses, a broader view towards 'brand' is developed and discussed in which the successful management of brands requires paying close attention to both the external customer franchise and the internal organisational system and culture.